Novas regulações na educação superior: do Estado Avaliador à acreditação em escala global (New regulations in higher education: from the Evaluative State to accreditation at the global scale) - Barreyro, Gladys Beatriz (Revista Eletrônica de Educação, 2019)
The text analyzes the transformation of the accreditation/evaluation) of higher education from a policy of the Evaluative State, in the ´80s, to a global policy with different modalities. Based on the concepts developed by Susan Robertson and Roger Dale in relation to the multi-scalar governance of higher education, it is shown the existence of accreditation policies at different scales, as well as the participation of different institutions and actors (international, private and non profit). The impact of the General Agreement on Trade and Services (GATS) in higher education, and specifically in evaluation/accreditation, generated policies such as global accreditation and regional accreditations. Also new institutions as accreditation agencies, and new strategies as guidelines for accreditation appeared, which are presented and analyzed in the text. It derives from a research, based on bibliography, documentary analysis and interviews with experts in internationalization and evaluation of higher education. Resumo O texto analisa a transformação da acreditação/avaliação da educação superior de uma política do Estado Avaliador na década de 1980 para uma política global desdobrada em diversas modalidades. A partir de conceitos desenvolvidos por Susan Robertson e Roger Dale acerca da governança multiescalar da educação, será mostrada a existência de políticas de avaliação em diversas escalas, assim como a participação de diversas instituições e atores (internacionais, privados e do terceiro setor). Mostra-se que o impacto do Acordo Geral de Comercio e Serviços (GATS) na educação superior e, especificamente na avaliação/acreditação, gerou políticas tais como o acreditador global e as acreditações regionais; e instituições como as agências de acreditação nacionais e/ou regionais e as redes dessas agências, que elaboram diretrizes apresentadas e analisadas no texto. Este é produto de pesquisa baseada em bibliografia, análise documental e entrevistas com especialistas em internacionalização e avaliação da educação superior. Resumen El texto analiza la transformación de la acreditación/evaluación de la educación superior de una política del Estado Evaluador, en la década de 1980, a una política global desdoblada en diversas modalidades. A partir de conceptos desarrollados por Susan Robertson y Roger Dale acerca de la gobernanza multiescalar de la educación superior, será mostrada la existencia de políticas de evaluación en diferentes escalas, así como la participación de diversas instituciones y actores (internacionales, privados y del tercer sector). Se afirma que el impacto del Acuerdo General de Comercio y Servicios (GATS) en la educación superior y, específicamente en la evaluación/acreditación, generó políticas tales como el acreditador global y las acreditaciones regionales e instituciones como las agencias de acreditación, las redes de agencias que elaboran directrices para acreditación que son presentadas y analizadas en el texto. Este deriva de una investigación, basada en bibliografía, análisis documental y entrevistas con especialistas en internacionalización y evaluación de la educación superior. Palavras-chave: Educação superior, Avaliação da educação superior; Acreditação, Governança multiescalar. Keywords: Higher education, Higher education evaluation, Accreditation, Multi-scalar governance. Palabras clave: Educación superior, Evaluación de la educación superior, Acreditación, Gobernanza multiescalar. References AFONSO, Almerindo Janela. Mudanças no Estado-avaliador: comparativismo internacional e teoria da modernização revisitada. Rev. Bras. Educ., Rio de Janeiro, v. 18, n. 53, p. 267-284, jun. 2013. AFONSO, Almerindo Janela. Avaliação educacional. Regulação e emancipação. 3ª. ed. São Paulo: Cortez, 2000. ALTBACH, Philip; KNIGHT, Jane. The internationalization of higher education: motivations and realities. Journal of Studies in International Education, v. 11, n. 3-4, p. 290-305, 2007. ANDERSON, Perry. Balanço do neoliberalismo. In: SADER, Emir; GENTILI, Pablo. Pós-neoliberalismo. As políticas sociais e o estado democrático. São Paulo: Paz e Terra, 1996. BARREYRO, Gladys Beatriz. A “Acreditação Mercosul” e a Agenda Interna da Política de Educação Superior Brasileira. SOUSA. A. S.Q.; CAMARGO, A. M.M. Interfaces da Educação Superior no Brasil. Curitiba: Editora CVR, 2014, p.49-61. BARREYRO, Gladys Beatriz. A avaliação da educação superior em escala global: da acreditação aos rankings e os resultados de aprendizagem. Avaliação, Campinas; Sorocaba, v. 23, n. 1, p. 5-22, mar. 2018. BARREYRO, Gladys Beatriz. O discurso da qualidade da educação superior e seus desdobramentos em políticas globais, regionais e nacionais. 2017. 174p. ils.; grafs.; anexos. Tese (Livre Docência). Faculdade de Educação da Universidade de São Paulo, São Paulo, 2017. BARREYRO, Gladys Beatriz; HIZUME, Gabriela de Camargo. Agências de avaliação e acreditação. In: ROTHEN, J. C; SANTANA, A. C. M. (Orgs.) Avaliação da educação: referências para uma primeira conversa. São Carlos: EDUFSCar, 2018a. pp. 67-79. Disponível em: http://www.edufscar.com.br/farol/edufscar/ebook/avaliacao-da-educacao-referencias-para-uma-primeira-conversa-(e-book)/52929/, acesso em 8 de jan. 2019. BARREYRO, Gladys Beatriz; HIZUME, Gabriela de Camargo. El Paraguay y la acreditación de carreras de grado en el Mercosur. Eccos. Revista científica. v. 47, p. 41-59, 2018b. BARREYRO, Gladys Beatriz; LAGORIA, Silvana Lorena. Acreditação da Educação Superior na América Latina: os casos da Argentina e do Brasil no Contexto do Mercosul. Cadernos PROLAM/USP, v. 9, p. 7-27, 2010. Disponível em: http://www.usp.br/prolam/downloads/2010_1_1.pdf BARREYRO, Gladys Beatriz; LAGORIA, Silvana Lorena; HIZUME, Gabriella de Camargo. As Agências Nacionais de Acreditação no Sistema ARCU-SUL: primeiras considerações. Avaliação, Campinas-Sorocaba, v. 20, n. 1, p.49-72, 2015. BARREYRO, Gladys Beatriz; ROTHEN, J. C. Percurso da avaliação da educação superior nos Governos Lula. Educação & Pesquisa, v. 40, n. 1, p. 61-76, 2014. BATISTA, J. P. El impacto de las negociaciones comerciales internacionales sobre la educación superior: los casos de Argentina y Brasil. Buenos Aires: Eudeba, 2012, 112 p. BLANCO RAMÍREZ, G. Quality by Association Across North-South Divides: United States Accreditation of Mexican Institutions of Higher Education. 2013. 220p. Tese (Doutorado em Política Educacional). Universidade Estadual de Massachussets-Amherst, 2013. BLUMENSTYK, G.; MCMURTRIE, B. Educators lament a corporate takeover of international accreditor. Chronicle of Higher Education. v. 47, n. 9, p. A55-57, out. 2000. CHEA INTERNATINAL QUALITY GROUP (CIQG). Frequently asked questions. Disponível em: http://www.chea.org/userfiles/uploads/ciqg-fact%20sheet-2014.pdf, acesso em jan. 2015. DALE, R. Globalisation, knowledge economy and comparative education. Comparative Education, v. 41, n. 2, p. 117-149, 2005. DIAS, M. A. R. Comercialização no ensino superior: é possível manter a ideia de bem público? Educ. Soc., Campinas, v.24, n.84, pp.817-838, set. 2003. DIAS SOBRINHO, J. Dilemas da educação superior no mundo globalizado. Sociedade do conhecimento ou economia do conhecimento. São Paulo: Casa do Psicólogo, 2005. DRAIBE, S. As políticas sociais no neoliberalismo. Revista da USP, Dossiê Liberalismo-neoliberalismo. São Paulo, n. 17, p. 86-101, 1993. EUROPEAN NETWORK FOR QUALITY ASSURANCE (ENQA). Criterios y Directrices para la Garantía de Calidad en el Espacio Europeo de Educación Superior. European Association for Quality Assurance in Higher Education, 2005, Helsinki. Disponível em: http://www.enqa.net/bologna.lasso., acesso em: 12 maio 2017. GENTILI, P. (org.) Pedagogia da exclusão. Crítica ao neoliberalismo em educação. Petrópolis: Vozes, 1995. GINKEN, H.; DIAS, M. A. Retos institucionales y políticos de la acreditación en el ámbito internacional. In: GLOBAL UNIVERSITY NETWORK FOR INOVATION (GUNI) La educación superior en el mundo. 2007. Acreditación para la garantía de la calidad: Qué está en juego? Madri: Ed. Mundi Prensa, 2006, p. 37-57. GLOBAL INITIATIVE FOR QUALITY ASSURANCE CAPACITY (GIQAC) Governance Terms, París, UNESCO, 2008. Disponível em: http://unesdoc.unesco.org/images/0015/001591/159197E.pdf, acesso em 19 maio 2017. HARTMANN, Eva. The United Nations Educational, Scientific and Cultural Organization: pawn or global player? Globalisation, Societies and Education, v.8, n. 2, 2010, p. 307-318, 2010. HIZUME, Gabriela de Camargo. A implementação do sistema de Acreditação Regional de Cursos Universitários do MERCOSUR: um estudo sobre as Agências Nacionais de Acreditação da Argentina e do Brasil. 2013. 260p. Dissertação (Mestrado) Programa de Pós-Graduação em Integração da América Latina, Universidade de São Paulo. São Paulo, 2013. HIZUME, Gabriela de Camargo; BARREYRO, Gladys Beatriz. A acreditação de cursos de graduação no Processo de Bolonha e no Mercosul. In: BARREYRO, G. B.; HIZUME, G. C. Regionalismos e inter-regionalismos na Educação Superior: projetos, propostas e influências entre a América Latina e a Europa. Coletânea submetida à editora da UNIOESTE, Cascavel, 2018, pp. 135-154. INTERNATIONAL NETWORK FOR QUALITY ASSURANCE AGENCIES IN HIGHER EDUCATION. INQAAHE Guidelines of Good Practice. Ed. Revisada, INQAAHE, 2016. Disponível em: http://www.inqaahe.org/sites/default/files/INQAAHE_GGP2016.pdf, acesso em 12 mai. 2017. LAURELL, Asa. Avançando em direção ao passado: a política social do neoliberalismo. In: LAURELL, Asa. (org.) Estado e políticas sociais no neoliberalismo. São Paulo: Cortez, 1995, p. 151-178. LIMA, Licínio; AZEVEDO, Mário Neves de; CATANI, Afrânio Mendes. O processo de Bolonha, a avaliação da educação superior e algumas considerações sobre a Universidade Nova. Avaliação (Campinas), Sorocaba, v. 13, n. 1, p. 7-36, mar. 2008. MARQUINA, Mónica. Tendencias recientes de los sistemas de evaluación de la educación superior en el actual escenario internacional. Un nuevo "round’ del Estado Evaluador? Avaliação (Campinas), v. 11, n. 4, p. 27-50, 2006. MICHAVILA, Francisco.; ZAMORANO, Silvia. La acreditación en el Espacio Europeo de Educación Superior. In: GLOBAL UNIVERSITY NETWORK FOR INOVATION (GUNI). La educación superior en el mundo. 2007. Acreditación para la garantía de la calidad: Qué está en juego? Madri: Ed. Mundi Prensa, 2006, p. 241-264. NEAVE, Guy. On the cultivation of quality, efficiency and enterprise: an overview of recent trends in higher education in Western Europe, 1986-1988. European Journal of Education, v.23, n.1/2, 1988, p. 7-23. NEAVE, Guy. Educación superior: historia y política. Barcelona: Gedisa, 2001. ROBERTSON, Susan. O processo de Bolonha da Europa torna-se global: modelo, mercado, mobilidade, força intelectual ou estratégia para construção do Estado? Revista Brasileira de Educação. v. 14, n. 42, p. 407-422. set./dez. 2009. ROBERTSON, Susan; DALE, Roger. Comparing policies in a globalising world: methodological reflections. Centre for Globalisation, Education and Social Futures. University of Bristol 2015a. Disponível em: https://edgesf.files.wordpress.com/2015/10/robertson-s-and-dale-r-2015-comparing-policies-in-a-globalising-world-methodological-reflections.pdf, acesso em 14 mai.2016. ROBERTSON, Susan; DALE, Roger. Critical cultural political economy of the globalisation of education, Globalisation, Societies and Education, v. 13, n. 1, p.149-170, 2015b. SGUISSARDI, Valdemar. O Banco Mundial e a educação superior: revisando teses e posições. In: Universidade brasileira no século XXI. Desafios do presente. São Paulo: Cortez Editora, 2009, p. 15-54. SGUISSARDI, Valdemar; BARREYRO, Gladys Beatriz. Evaluación/regulación de la educación superior en el Brasil: algunos aspectos históricos y actuales. Profesorado, revista de curriculum y formación del profesorado. v. 20, n.3, p. 171-206, 2016. STUBRIN, Adolfo Luis. Los mecanismos nacionales de garantía pública de calidad en el marco de la internacionalización de la educación superior. Avaliação, v. 10, n. 4, p. 9-22, 2005. UNESCO. Global Initiative for Quality Assurance Capacity (GIQAC) Governance Terms. Paris, UNESCO, 2008. Disponível em: http://unesdoc.unesco.org/images/0015/001591/159197E.pdf, acesso em 15 maio 2017 UNESCO; OECD. Guidelines for Quality Provision in Cross-border Higher Education, Paris, 2005. Disponível em: http://unesdoc.unesco.org/images/0014/001433/143349e.pdf, acesso em 3 abr. 2017. UVALIC-TRUMBIC, Stamenka. Política internacional de garantía de la calidad y acreditación: de los instrumentos legales a las comunidades de práctica. In: GLOBAL UNIVERSITY NETWORK FOR INOVATION (GUNI). La educación superior en el mundo. 2007. Acreditación para la garantía de la calidad: Qué está en juego? Madri: Ed. Mundi Prensa, 2006, p. 58-72. VAN DAMME, Dirk. Trends and models international quality assurance and accreditation in higher education in relation to trade in education services. OECD/US Fórum on Trade in Educational Services. 23-24 may. 2002. Washington, DC. Disponível em: http://www.oecd.org/education/skills-beyond-school/2088479.pdf , acesso em 25 mar. 2017. VERGER, Antoni; HERMO, Javier. The governance of higher education regionalisation: comparative analysis of the Bologna Process and Mercosur educativo. Globalisation, Societies and Education, v. 8, n.1, p. 105-120, mar. 2010. WELLS, Peter. The DNA of a converging diversity: regional approaches to quality assurance in higher education, CHEA, 2014. Disponível em: https://www.chea.org/userfiles/Conference%20Presentations/DNA_Converging_Diversity.pdf, acesso em 8 maio 2017. WORLD BANK. Higher education: the lessons of experience. Washington: The World Bank Group, 1994. WORLD BANK. The financing and management of higher education – A status report on worldwide reforms. Elaborado por D. Bruce Johnstone, com colaboração de Alka Arora e William Experton. Washington: The World Bank, 1998. WORLD BANK. task Force on Higher Education and Society. Higher education in developing countries: peril and promise. Washington, DC: The World Bank, 2000.